Beta blockers and chronic heart failure patients: prognostic impact of a dose targeted beta blocker therapy vs. heart rate targeted strategy - Corletto, Anna; Fröhlich, Hanna; Täger, Tobias; Hochadel, Matthias; Zahn, Ralf; Kilkowski, Caroline; Winkler, Ralph; Senges, Jochen; Katus, Hugo; Frankenstein, Lutz (Clinical research in cardiology, 2018)
BackgroundBeta blockers improve survival in patients with chronic systolic heart failure (CHF). Whether physicians should aim for target dose, target heart rate (HR), or both is still under debate.Methods and ResultsWe identified 1,669 patients with systolic CHF due to ischemic heart disease or idiopathic dilated cardiomyopathy from the University Hospital Heidelberg and the Clinic of Ludwigshafen, Germany. All patients were treated with an angiotensin converting enzyme inhibitor or angiotensin receptor blocker and had a history of CHF known for at least 6 months. Target dose was defined as treatment with ≥ 95% of the respective published guideline-recommended dose. Target HR was defined as 51-69 bpm. All-cause mortality during the median follow-up of 42.8 months was analysed with respect to beta blocker dosing and resting HR. 201 (12%) patients met the dose target (group A), 285 (17.1%) met the HR target (group B), 627 (37.6%) met no target (group C), and 556 (33.3%) did not receive beta blockers (Group D). 5-year mortality was 23.7, 22.7, 37.6, and 55.6% for group A, B, C, and D, respectively (p < 0.001). Survival for group A patients with a HR ≥ 70 bpm was 28.8% but 14.8% if HR was 50-70 bpm (p = 0.054).ConclusionsAchieving guidelines recommended beta blocker dose or to HR control has a similar positive impact on survival. When on target dose, supplemental HR control additionally improves survival.
Published online: 17 May 2018
Gesehen am 28.06.2019